Bioinformatics of edible yellow mealworm (Tenebrio molitor) proteome reveal the cuticular proteins as promising precursors of dipeptidyl peptidase‐IV inhibitors. Issue 2 (14th December 2019) - Dávalos Terán, Irene; Imai, Kento; Lacroix, Isabelle M. E.; Fogliano, Vincenzo; Udenigwe, Chibuike C.
Abstract: Bioinformatics was applied for strategic processing of yellow mealworm ( Tenebrio molitor ) proteins to produce dipeptidyl peptidase (DPP)‐IV inhibiting peptides. In silico analysis of 384 mealworm proteins revealed structural proteins as better precursors of DPP‐IV inhibiting peptides, compared with other protein types, after pepsin and papain hydrolysis. This was associated with the higher hydropathicity and amounts of residues associated with DPP‐IV inhibition in the structural (cuticular) proteins. In silico, the peptides were mostly released with pepsin than papain. Cuticular (CP) and non‐cuticular proteins (NC) were extracted from yellow mealworm and hydrolyzed with pepsin and papain in vitro to validate the virtual findings. CP hydrolysate with papain inhibited DPP‐IV the most compared to CP hydrolysate with pepsin, whereas NC hydrolysates were mostly inactive. CP had higher hydrophobic–hydrophilic amino acid ratios and contents of the activity‐associated residues than NC. The findings demonstrate the application of bioinformatics in processing proteins for bioactive peptide production. Practical applications: The discovery of bioactive peptides from food proteins is typically based on the classic approach involving working with a small number of protein‐protease combinations in vitro. For the first time, this study reported the application of in silico tools in comprehensively studying hundreds of proteins from yellow mealworm (an edible insect) as sources of DPP‐IV inhibitors, followed by in vitro processing and validation guided by the results obtained in silico. The advantage of this approach is that it allows for analysis of several protein–protease combinations (with multiple datasets of structural, functional, and bioactivity parameters) in a short time. This work is relevant in advancing research on emerging or alternative proteins as well as structure‐informed food protein processing. The bioinformatics approach can be adapted for strategic processing of proteins in the food industry prior to making major resource investments. Abstract : Bioinformatics showed structural proteins of edible mealworm to be better precursors of DPP‐IV inhibiting peptides than other protein types. In vitro assessments with mealworm cuticular and non‐cuticular proteins validated the in silico findings. This approach enables structure‐informed protein processing for bioactive peptide production.